Reproductive Biology of Feather Back, Chital (Notopterus chitala, Ham.) Cultured in a Pond of Bangladesh (International Journal of Agricultural Research, Innovation and Technology, 2013)
Studies on Gonadosomatic index (GSI), ova diameter and histology of the gonad were performed to understand reproductive biology of Feather back, Chital (Notopterus chitala) for a period of 6 months from January to June 2010. Thirty live chital fish were used in this study. The mean GSI values for female chital were found to range between 0.20±0.013 and 4.63±0.50. The highest GSI value was found in June. The smallest diameter of ovum was recorded 0.04 mm (January) and the largest was 4.00 mm (June). During the experimental period, the fecundity was ranged from 8,238 to 18,569 (mean 13,052±4607) in fish samples with body weight range from 1,296 to 2,360 (mean 1,742.50±474.44 g) while the relative fecundity was 5.65 to 14.33. Histological study revealed that the percentage of late perinucleolus (LPN) stage was highest in April and Cortical alveoli (CA) stage appeared from April and reached to maximum in May. Vitellogenic stage (VG) appeared in the month of May and chronologically increased through June. Vitellogenic stage (VG) of oocyte as well as highest ova diameter reached to the peak in June. The variations in the gonad weight and GSI of the female fish reached to the peak during June indicating maturity of ovary and definite spawning season. DOI: http://dx.doi.org/10.3329/ijarit.v2i1.13991 Int. J. Agril. Res. Innov. & Tech. 2 (1): 26-31, June, 2012